2016
DOI: 10.1080/1354750x.2016.1201534
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor, growth differentiation factor-15, and survivin as novel biocompatibility markers in children on chronic dialysis

Abstract: Context: Chronic dialysis results in aggravation of apoptosis and cell damage, triggered by bioincompatibility of dialysis membranes and peritoneal fluids.Objective: The aim of study was to assess the usefulness of epidermal growth factor (EGF), growth differentiation factor (GDF)-15 and survivin as novel markers of biocompatibility in dialyzed children. Material and methods: Parameters were assessed by ELISA in 19 patients on hemodialysis and 22 children on peritoneal dialysis. Results: Serum concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
(4 reference statements)
1
3
0
Order By: Relevance
“…Also, the diagnostic performance of GDF-15 as a marker of inflammation in CKD was comparable to CRP and better than ferritin that is mostly elevated by iron overload associating CKD, qualifying GDF-15 as a surrogate marker of inflammatory status in CKD. Similar results were found by Bargenda et al [ 27 ], Thorsteinsdottir et al [ 28 ]…”
Section: Discussionsupporting
confidence: 92%
“…Also, the diagnostic performance of GDF-15 as a marker of inflammation in CKD was comparable to CRP and better than ferritin that is mostly elevated by iron overload associating CKD, qualifying GDF-15 as a surrogate marker of inflammatory status in CKD. Similar results were found by Bargenda et al [ 27 ], Thorsteinsdottir et al [ 28 ]…”
Section: Discussionsupporting
confidence: 92%
“…Urinary GDF-15 levels have also been shown to be elevated and negatively correlated with eGFR in adults with diabetes [8]. Increasing data exists on GDF-15 in children, but only one study on children with kidney disease is published and demonstrates elevated GDF-15 levels in patients on hemodialysis and peritoneal dialysis [9].…”
Section: Introductionmentioning
confidence: 99%
“…After confirming the absence of multicollinearity, we performed multivariate analysis for each biomarker while including the confirmed adjustment variables. Previous research has demonstrated that the biomarkers in our study interact with each other [ 15 , 26 28 ]. Therefore, we have chosen to analyze each biomarker individually rather than using a multivariate regression analysis.…”
Section: Methodsmentioning
confidence: 69%